Dividend payment behaviour and its determinants: The Nigerian evidence - Abdulkadir, Rihanat Idowu; Abdullah, Nur Adiana Hiau; Wong, Woei Chyuan (2014)
This paper examines the disappearing dividend phenomenon within the Nigerian context by observing dividend patterns between year 2003 to 2012.We investigate possible explanation for the pattern observed by examining factors that determine a firm's decision to pay or not to pay dividends.Findings indicate a decline in the number of firms paying dividends and a downward trend in nominal dividends paid in latter years. Fixed effect logistic estimates indicate that firms with higher level of foreign ownership are less likely to pay dividends. Our findings therefore provide support for the tax-induced clientele theory of dividends.The study also provide support for profitability as a characteristic of a dividend payer and support for dividend smoothing hypothesis. However, we did not find evidence in support of the catering theory and the life cycle theory of dividend.